Investigating the mediating role of character strengths and virtues in the relationship between gender and positive and negative excitements of elementary teachers in the classroom - Seyed Alireza Hashemi; Mohsen Shakeri; Kazem Barzegar Bafrooei; Mahdieh Estabraghi (Allameh Tabataba'i University Press, 2023)
The aim of this study was to investigating the mediating role of character strengths and virtues in the relationship between gender and positive and negative excitements of elementary teachers in the classroom. The present study was a fundamental research that falls into the category of descriptive research and more precisely correlation of structural equations. The statistical population of this study included all primary school teachers in the academic year 2020-21 in Ashkzar city, numbering 207 people; all the people were selected using the total number method. The Peterson and Seligman (2004) Character Strengths and Virtues Questionnaire and the Villainscience (2010) Teaching Excitements Questionnaire were used to collect research data. Data were analyzed using SPSS and Amos software at both descriptive and inferential levels. The results of structural equation modeling showed that gender positively and significantly (β = 0.55) predicts character strengths and virtues. The findings also showed that character strengths and virtues positively and significantly (β = 0.31) predict positive teaching excitements and negatively and significantly predict negative teaching excitements (β = -0.43). Examination of model fit indices also showed that the final research model has a good fit. Therefore, it can be concluded that by strengthening the character strengths and virtues of elementary teachers, the experience of positive excitements in teaching can be increased to some extent and the experience of negative excitements can be reduced.